Antioxidant activity synergy between stingless bee honey and sea cucumber extract combination for food supplement - Mohd Azman, Amier Asyraf Bin; Mohamed Rehan, 'Aisyah; Mohd Fauzi, Noor Akhmazillah; Kamarudin, Kamarul Rahim (Progress in Engineering Application and Technology, 2022)
Contemporary research has shown that the local tradition of stingless bee honey consumption has potential for additional value in modern medicine and has a higher therapeutic value than other species of bee. Recently, it has been found that stingless bee honey is a unique source of trehalulose, a physiologically active disaccharide that offers several health advantages, especially those coming from Malaysian Geniotrigona thoracica honey. Sea cucumbers have for a long time been used for food and folk medicine. Sea cucumbers are widely known for their efficacy against high blood pressure, asthma, wounds and brushes, impotence, and constipation in Chinese and Malaysian. Both the stingless bee and the sea cucumber are present in Malaysia, along with native species. Combination with stingless bee honey can be commercially beneficial for the food supplement industry. Synergistic between sea cucumber and stingless bee honey will be assessed in this study. The aim of this research is to investigate the synergy of antioxidants by combining sea cucumber extract with stingless bee honey for potential food supplement. The objective of this study is, to perform antioxidant experiment on sea cucumber extract and stingless bee honey, to determine the synergistic effect of sea cucumber extract with stingless bee honey by antioxidant synergy and determine the appropriate ratio between stingless bee honey and sea cucumber in producing an effective antioxidant. Malaysian kelulut honey has excellent potential to be marketed further if the products can be diversified further through combination with other natural product to produce a novel supplement combination. It is hoped that this study could be a starting point to investigate the potential of combining kelulut honey with sea cucumber extract as a novel functional supplement.